Pemanfaatan Novel Si Anak Cahaya Karya Tere Liye sebagai Media Literasi Penguatan Profil Pelajar Pancasila - Ariani, Shepta Juni; Rakhmawati, Ani; Setiyoningsih, Titi (Universitas Negeri Surabaya, 2024)
The aim of this research is to determine the benefits of the novel Si Anak Cahaya by Tere Live as a literacy medium in an effort to strengthen the Profil Pelajar Pancasila. This research will focus the analysis of the novel on the dimensions of the Profil Pelajar Pancasila obtained through the attitudes and actions of the main character. This research is a qualitative descriptive research with a novel content analysis method. Descriptive research is research carried out by providing an overview of research results. The document data source used is the novel entitled Si Anak Cahaya by Tere Liye. The sampling technique used in this research is purposive sampling, namely a sampling technique that is based on certain considerations, objectives and reasons. The results of this research are that the novel Si Anak Cahaya by Tere Liye contains the dimensions of the Profil Pelajar Pancasila, namely: (1) having faith, being devoted to God Almighty, and having noble morals: (2) working together: (3) being independent; (4) critical reasoning; and (5) creative. Based on the results and discussions that have been obtained, it can be concluded that the novel Si Anak Cahaya is suitable to be used as a media for literacy and strengthening the Profil Pelajar Pancasila in high school. This novel can be used as an alternative reading in literacy activities at school and as an alternative activity for the Projek Penguatan Profil Pelajar Pancaasila (P5) Keywords: Novel, Media for Literacy, Profil Pelajar Pancasila